DETERMINANTS OF BANK BUSINESS RISK ACCORDING TO RISK-BASED BANK RATING COMPONENTS APPROACH (A CASE IN COMMERCIAL BANKS THAT LISTED ON INDONESIA STOCK EXCHANGE) - Haryakusuma, Kurnia; Indrawati, Nur Khusniyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Banks have important role on economy of Indonesia, with a fully-regulated principle, Banking Sectors in Indonesia concern to keep in a good performance according to Indonesia Bank Rules No. 13/1/PBI/2011 which emphasize on risk-based approach. Therefore, it is interesting to know the factors that affect commercial banks’ business risk that listed on Indonesia Stock Exchange. Those factors consist of risk profile (credit risk, liquidity risk, and interest rate risk), good corporate governance, earnings, and capital. The sample used in this researsh are 26 commercial banks that listed on Indonesia Stock Exchange during research period since 2011-2013. This research uses multiple linear regression analysis. The result of the findings are credit risk has effect against business risk. While, liquidity risk does not have effect against business risk. Interest rate risk has effect against business risk. Good corporate governance does not have effect against business risk. Earnings has significant effect against business risk. Capital does not have effect against business risk. Hence, the entire implication of the research is commercial banks’ business risk is affected by three factors from risk-based bank rating (credit risk, interest rate risk, and earnings). Keywords: Risk-Based Bank Rating, Credit Risk, Liquidity Risk, Interest Rate Risk, Good Corporate Governance, Earnings, dan Capital, Bank’s business risk